2019
DOI: 10.1016/j.redox.2019.101142
|View full text |Cite
|
Sign up to set email alerts
|

Protein disulfide isomerase plasma levels in healthy humans reveal proteomic signatures involved in contrasting endothelial phenotypes

Abstract: Redox-related plasma proteins are candidate reporters of protein signatures associated with endothelial structure/function. Thiol-proteins from protein disulfide isomerase (PDI) family are unexplored in this context. Here, we investigate the occurrence and physiological significance of a circulating pool of PDI in healthy humans. We validated an assay for detecting PDI in plasma of healthy individuals. Our results indicate high inter-individual (median = 330 pg/mL) but low intra-individual variability over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 66 publications
0
17
1
1
Order By: Relevance
“…Oliveira et al have recently shown that PDI plasma levels may discriminate apparently healthy individuals bearing distinct plasma proteome patterns, suggestive of cardiovascular and immunoinflammatory risk 73 . The median plasma levels were 330 pg/ml with high interindividual variability, but low intraindividual variability.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oliveira et al have recently shown that PDI plasma levels may discriminate apparently healthy individuals bearing distinct plasma proteome patterns, suggestive of cardiovascular and immunoinflammatory risk 73 . The median plasma levels were 330 pg/ml with high interindividual variability, but low intraindividual variability.…”
Section: Discussionmentioning
confidence: 99%
“…70 The prothrombin time and partial thromboplastin time coagulation assays were not prolonged. 73 The median plasma levels were 330 pg/ml with high interindividual variability, but low intraindividual variability.…”
Section: Other Subs Tr Ate S Of Prothromboti C Pd Is In Thrombos Ismentioning
confidence: 94%
“…The true role of this protein here is unclear, but one can hypothesize that GPx8 could be involved in the maintenance of protein disulfide isomerase (PDI), which in ER acts in protein folding, since GPx8 and GPx7 may accept PDI as a reductant more efficiently than does GSH [ 11 ]. Moreover, a recently published study suggested that PDI is present in human plasma at important levels and could be even used as a marker for some medical conditions [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…7 ). Among them, heat shock protein 90 kDa α (HSP90 α) is a potential factor driving the wound’s expected closure [ 24 ], while deficiency of protein disulfide isomerase (PDI), resulting in trauma-related migration and recovery area [ 25 ]. Tubulin alpha chain (TAC) may be involved in PLAB-mediated apoptosis of hypertrophic scar fibroblasts, and elongation factor 1-α 1 (EF-1α) potentially participate in scarless healing [ 26 , 27 ].…”
Section: Resultsmentioning
confidence: 99%